2013
DOI: 10.3389/fimmu.2013.00172
|View full text |Cite
|
Sign up to set email alerts
|

Re-Directing CD4+ T Cell Responses with the Flanking Residues of MHC Class II-Bound Peptides: The Core is Not Enough

Abstract: Recombinant αβ T cell receptors, expressed on T cell membranes, recognize short peptides presented at the cell surface in complex with MHC molecules. There are two main subsets of αβ T cells: CD8+ T cells that recognize mainly cytosol-derived peptides in the context of MHC class I (pMHC-I), and CD4+ T cells that recognize peptides usually derived from exogenous proteins presented by MHC class II (pMHC-II). Unlike the more uniform peptide lengths (usually 8–13mers) bound in the MHC-I closed groove, MHC-II prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 63 publications
(76 reference statements)
7
67
0
1
Order By: Relevance
“…As more hydrogen bonds are formed between the receptor and the predicted epitope, the Isc value is lower, i.e., the complex has a higher binding affinity, emphasizing the fact that the peptides bind to the MHC alleles (particularly MHC II) via an “extensive hydrogen bond network” (28). To further investigate this correlation, three complexes included in the final results (FPD500) were selected and analyzed (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…As more hydrogen bonds are formed between the receptor and the predicted epitope, the Isc value is lower, i.e., the complex has a higher binding affinity, emphasizing the fact that the peptides bind to the MHC alleles (particularly MHC II) via an “extensive hydrogen bond network” (28). To further investigate this correlation, three complexes included in the final results (FPD500) were selected and analyzed (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Only peptides containing at least nine AAs were taken into account, as this is the minimal size for binding to MHC class II molecules and subsequent T cell recognition. 16…”
Section: Ms Data Analysismentioning
confidence: 99%
“…However, it has been shown that peptide flanking regions (PFRs) on either side of the binding core affect peptide-MHC binding and, thereby ultimately also influence the peptide immunogenicity. 7,9 There are therefore many factors that make it difficult to predict peptide binding affinities to MHC-II molecules, including the polymorphic nature of MHC-II molecules, the variations in peptide length, the influence of the PFRs and the identification of the correct peptide binding core. All these factors complicate the task of predicting peptide binding affinities to MHC-II molecules; most methods therefore still have a low performance compared with MHC class I (MHC-I) peptide binding prediction methods.…”
Section: Introductionmentioning
confidence: 99%